Structuring servitization-related research - Rabetino, Rodrigo; Harmsen, Willem; Kohtamäki, Marko; Sihvonen, Jukka (Emerald, 2018)
Purpose - The purpose of this paper is to organize and connect past research from different servitization-related scholarly communities. Design/methodology/approach - This study reviews more than 1,000 articles by combining author co-citation and qualitative content analyses. Findings - The structure and boundaries of the field are mapped, and the characteristics of the three identified servitization-related communities are assessed qualitatively. These three communities are product-service systems, solution business, and service science. The findings demonstrate that a narrow range of theories and qualitative methods dominate in existing research. Originality/value - Through the lens of the sociology of science, this review critically evaluates servitization-related research and offers a list of themes that are considered important to the future development of the field. Regarding future research, the main recommendations are as follows: increasing the use of well-established theories from adjacent mature fields, borrowing ideas from different research communities to stimulate knowledge accumulation within and across communities, and reducing the level of description while increasing the number of confirmatory, quantitative, and longitudinal research designs. Finally, the development of formal structures for socialization (e.g. conferences and special issues) could allow the field to achieve a greater degree of scientific maturity and would influence the direction and pace of the development of servitization-related research.
Keywords: bibliometric analysis; integrated solutions; product-service systems; service infusion; servitization; fi=Johtaminen ja organisaatiot|en=Management and Organization|